2018
DOI: 10.12688/f1000research.13426.1
|View full text |Cite
|
Sign up to set email alerts
|

NFAT control of immune function: New Frontiers for an Abiding Trooper

Abstract: Nuclear factor of activated T cells (NFAT) was first described almost three decades ago as a Ca 2+/calcineurin-regulated transcription factor in T cells. Since then, a large body of research uncovered the regulation and physiological function of different NFAT homologues in the immune system and many other tissues. In this review, we will discuss novel roles of NFAT in T cells, focusing mainly on its function in humoral immune responses, immunological tolerance, and the regulation of immune metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
137
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 123 publications
(200 reference statements)
2
137
0
Order By: Relevance
“…The decreased NFAT levels might lead to the altered Treg cells profile by further affecting the NFAT:FOXP3 complex formation (Figure ). In induced Tregs (iTregs), NFATs regulate the expression of FOXP3 by binding to the Cis‐regulatory element of FOXP3 CNS1 (Vaeth & Feske, ). Studies with double‐deficient NFAT mouse models ( NFAT 1, 2, and 4 knockout mice) also reported a diminished FOXP3 expression by iTregs (Kwon et al, ; Vaeth et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased NFAT levels might lead to the altered Treg cells profile by further affecting the NFAT:FOXP3 complex formation (Figure ). In induced Tregs (iTregs), NFATs regulate the expression of FOXP3 by binding to the Cis‐regulatory element of FOXP3 CNS1 (Vaeth & Feske, ). Studies with double‐deficient NFAT mouse models ( NFAT 1, 2, and 4 knockout mice) also reported a diminished FOXP3 expression by iTregs (Kwon et al, ; Vaeth et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The NFAT:FOXP3 complex regulates the Treg function by upregulating the expression of suppressive genes like CTLA4, IL10, TGFB, and downregulating the expression of IL2 and IL4. However, the disruptive mutations and the altered levels of NFAT:FOXP3 complex lead to non‐functional Tregs (Figure ) (Vaeth & Feske, ). Since we found decreased expression of both NFATs and FOXP3, we further assessed their effect on downstream immune‐suppressive genes in Tregs of GV patients.…”
Section: Discussionmentioning
confidence: 99%
“…Creation of the congenic SHR-A3(Stim1-B2) line demonstrates that rescue of defective Stim1 function prevents development of cerebrovascular disease in SHR-A3 while restoring T helper cell functions. Stim deficiency limits the ability of T helper cells to provide effective help to B cells as the latter undergo antibody affinity maturation [16,36]. This results in premature termination of affinity maturation and the development of antibody-secreting cells that generate self-reactive antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the best understood functions of CN in mammals are in regulation of the immune system (Hogan et al, 2003;Vaeth and Feske, 2018), recent evidence suggests it also plays a part in the stress response (Medina et al, 2015;Zhang et al, 2016). Oxidative stress and nutrient limitation both lead to the release of intracellular Ca 2+ stores that activate CN.…”
Section: Discussionmentioning
confidence: 99%